2010
DOI: 10.1590/s1808-86942010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Função da tuba auditiva em adultos com membrana timpânica íntegra

Abstract: The Eustachian tube has the function of equilibrating the environmental pressure with inner pressure, protecting the middle ear from abrupt pressure changes. Aim:To compare the Eustachian tube function in adults with and without history of otitis media and/or respiratory tract inflammation without tympanic membrane perforation. Materials and Methods:The Eustachian tube function was evaluated in forty-two females and males of 18 to 55 years of age with intact tympanic membrane, tympanometric A curves and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…[19]. Tympanometry, an objective test, is a simple manometric test that can provide an indirect measure of E-tube function by measuring the pressure of the middle ear [8]. Using tympanometry, Doyle et al reported that the Valsalva maneuver had sensitivity and specificity of 55% and 85% in discriminating between E-tube dysfunction and normal [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19]. Tympanometry, an objective test, is a simple manometric test that can provide an indirect measure of E-tube function by measuring the pressure of the middle ear [8]. Using tympanometry, Doyle et al reported that the Valsalva maneuver had sensitivity and specificity of 55% and 85% in discriminating between E-tube dysfunction and normal [20].…”
Section: Discussionmentioning
confidence: 99%
“…Since E-tube dysfunction can lead to diverse otologic diseases [8,12,19], it is essential to address and manage the function of the E-tube in managing patients with ear diseases. The clinical significance of our study includes that the treatment of sinusitis improves E-tube dysfunction, so clinicians should always try to seek and manage possible sinusitis that will affect E-tube function and thus influence the otologic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have looked at functional ETD testing in children, this is the first to attempt to define a normal value for these tests (4,6,10,11). We have demonstrated that the adult norm of +20 daPa shift in pressure after Valsalva can likely be applied to children over the age of 12.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The only muscle responsible for opening the tube is the tensor muscle of the soft palate, which when contracted promotes ventilation of the middle ear 6 . This mechanism protects the ear from rapid pressure changes, keeps the mucosa preserved and allows the eardrum -ossicular unit to vibrate uneventfully 7 . Muscular changes in the palate may entail a reduction of tubal functioning 8 .…”
Section: Introductionmentioning
confidence: 99%